دراسة تأثير تغيير بعض العوامل المؤثرة على استقرار الستائر الإسفلتية المستخدمة في تكتيم السدود بالظروف السورية - سماح محمد (Tishreen University, 2016)
Asphalt concrete was used for the first time in Syria as a tightening material for dam Sourani. It was used in this dam as a surface facing on the front slope. Use of asphaltic concrete under climatic conditions prevailing in Syria, particularly high temperatures, is discussed in the paper. To achieve this goal, a number of bituminous concrete mixes, designed using the same constituent components in Sourani dam, were experimentally tested and analyzed. To determine the effect of the expected maximum temperatures for Sourani dam, a program depending on Energy balance was developed. Possible methods of reducing the effect of the high temperature in order to increase the stability of the asphalt surface facing are analyzed. In this context, the facing was plastered by a light-color, which led to a decrease in the temperature of the asphalt surface facing by about 20 degrees Celsius. The facing was also plastered by placing a concrete layer above it, which led to a decrease in the temperature of the asphalt surface facing by about 25 degrees Celsius. استُخدم البيتون الاسفلتي للمرة الأولى في سورية كمادة مانعة للرشح في السدود على شكل ستارة على السفح الأمامي في سد الصوراني، و نظراً لدرجات الحرارة العالية التي يمكن أن تتعرض لها الستارة الاسفلتية في ظروف سورية، و تأثير ارتفاع درجة الحرارة على استقرار البيتون الاسفلتي المتوضع على طبقات مائلة مما يؤدي إلى زيادة قابليته للزحف نحو الأسفل ليس فقط بتأثير مركبة الوزن الذاتي، و إنما أيضاً بسبب المقاومة المرنة و اللزجة التي تبديها مادة البيتون الاسفلتي ضد الحركة، و التي سببها الرئيسي لزوجة البيتون الاسفلتي، التي تتأثر بشكل كبير بدرجة الحرارة التي يتعرض لها، و عند ارتفاع الحرارة بشكل كبير قد تؤدي إلى تخريب الستارة الاسفلتية. دُرست في البحث طرائق خفض هذه الحرارة بالطرائق الممكنة من أجل زيادة استقرار الستارة الاسفلتية السطحية و ذلك بطلائها بلون فاتح فانخفضت درجة حرارتها بنحو 20درجة مئوية، و بوضع طبقة من البيتون الاسمنتي فوقها، و هو ما أدى إلى خفض درجة الحرارة على سطحها بنحو 25 درجة مئوية.